Modal Psikologis dan Persepsi Dukungan Organisasi terhadap Kesiapan Individu untuk Berubah pada Pegawai PPPKP-KKP - Fadiah Adlina; Endro Puspo Wiroko; FD Wara Timur Hayuwardhani (Psympathic : Jurnal Ilmiah Psikologi, 2018)
This study aimed to determine the effect of psychological capital and perception of organizational support for individual readiness to change among employees. This study used correlational (non-experimental) method. By using disproportionate stratified random sampling, there were 62 participants in Center of Marine and Fisheries at the Ministry of Marine Affairs and Fisheries. The measuring tools used in this study were Readiness for Change Scale (RFC), Psychological Capital Questionaire (PCQ), and Survey of Perceived Organizational Support (SPOS) which all of them have been adapted into Bahasa Indonesia. Data analysis technique used in this research was multiple linear regression. Result of this study indicated that psychological capital and perception of organizational support simultaneously can give significant effect to individual readiness to change.